Yksinäisyyden yhteys nuorten terveyskäyttäytymiseen : suunterveyden näkökulma - Yrjölä, Wilhelmina (2024)
The role of oral health in an individual's overall health is great and affects not only the individual's health but also their general quality of life. According to previous studies, loneliness has a negative effect on an individual's health and increases health behaviors that are harmful to health, but the connection between oral health care and loneliness has been studied only a little. The aim of this master's thesis was to find out the implementation of oral health care in Finnish youth and the connections between loneliness experienced by young people and oral health care. In addition to this, the aim was to find out the factors that were connected to poor oral health care in both lonely and non-lonely youngsters. The health behaviors that affect oral health, which the study paid attention to in addition to tooth brushing, were related to young people's eating habits and substance use. Factors whose connections to poor oral health care were examined in addition to health behaviors were social factors and gender of young people.